Desvendando os sentidos atribuídos por egressos do PETMAT/UFG à atividade pedagógica do professor de matemática - Macedo, Adriane Sardinha (2017)
In this research we are looking for indications of the meanings attributed by the graduates of PETMAT / UFG, professor of mathematics, to the pedagogical activity. Vigotski, Leontiev, Moura, Cedro, Engeström and Asbahr were fundamental for the apprehension of the object searched. We focus on historical-cultural theory as a basis for the apprehension of the phenomenon investigated and, for this, the theory of activity was present throughout the work. Our research was based on a bibliographical research, a documentary analysis in which we evaluated the documents that underpin the organization of the Tutorial Education Program (PET) and, from there, we made a documentary comprehension movement of the Tutorial Education Program of the Education Teachers in Mathematics from the Federal University of Goiás (PETMAT / UFG). We analyze all the tasks and projects developed in the program over the years 2007 to 2014 and, in addition to this, we interviewed some alumni who were linked to the group during those years. The teacher-tutor of the group was also part of our work and is among the subjects participating in the research. The activity, the social meaning and the personal sense are presented in the work, based on the Leontievian proposal. For the analysis of the data, we proposed two categories: [1] the personal sense of the future teacher about the Pedagogical Activity of the mathematics teacher; and [2] the PETMAT / UFG and its contradictions as a source of change and development. In the first category we conclude that individuals, starting from the indigence of joining a university, from the influences of their teachers, and from the affinity they believe they had with the exact areas, hoped to graduate. There are those who were looking for the teaching or marketing of the pre-college preparatory teacher; and there were others who wanted a training in Mathematics that was not destined to be performed in the classroom. In the second category, we analyzed some projects carried out in PETMAT / UFG and supported them in Engeström (1999 and 2009) and, from there, we constructed some Activity Systems. By introducing such systems we intend to propose that, instead of the socially mediated individual being taken as the basic unit of analysis, the historically localized system of activity has become a fundamental unit for looking at egresses in the collective as well. The object of activity as a horizon of possibility is, in the Engeströmapproach, theorized as a collective project that is stabilized by shared tools, signals, and procedures. The results allowed us to perceive the necessity of a differentiated proposal for the formation of the mathematics teacher, in which the teaching learning organization allows the collective work as organization of a non-alienated work, making possible the construction of a knowledge production space.